1997
DOI: 10.1046/j.1464-410x.1997.08835.x
|View full text |Cite
|
Sign up to set email alerts
|

False‐positive prostatic‐specific antigen in the serum of a man with renal cell carcinoma

Abstract: Fig. 1. A, Diagnostic MRI and, B, 1 year after treatment shows almost complete involution of an orbital metastasis of a prostatic adenocarcinoma. Case reports Cases 1 and 2A 76-year-old man (patient A) and an 83-year-old man (patient B) were examined in 1993 by the ophthalmologist because of diplopia due to progressive unilateral exophthalmus. CT and MRI in both instances showed locally destructive tumours in the right (patient A) and left (patient B) orbital bony and soft tissues. Biopsies revealed adenocarci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Of note is the study by Douville and Tiberi, 70 which demonstrated normal total PSA concentrations but signi®cantly higher free PSA levels in patients on chronic haemodialysis, suggesting that the cut-off value established for non-renal patients may be inappropriate. Raised levels of PSA have been detected in the serum of men 71 and women 72 with renal cell carcinoma, PSA levels returning to normal following nephrectomy. Interference by other kallikreins may be implicated in the ®rst of these reports, as polyclonal antibody was used in the assay.…”
Section: Psa In Non-prostatic Illnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note is the study by Douville and Tiberi, 70 which demonstrated normal total PSA concentrations but signi®cantly higher free PSA levels in patients on chronic haemodialysis, suggesting that the cut-off value established for non-renal patients may be inappropriate. Raised levels of PSA have been detected in the serum of men 71 and women 72 with renal cell carcinoma, PSA levels returning to normal following nephrectomy. Interference by other kallikreins may be implicated in the ®rst of these reports, as polyclonal antibody was used in the assay.…”
Section: Psa In Non-prostatic Illnessmentioning
confidence: 99%
“…Interference by other kallikreins may be implicated in the ®rst of these reports, as polyclonal antibody was used in the assay. 71 A report by Garcia Reboll et al 73 suggested that the hypogonadism associated with renal failure may reduce prostatic growth. It might be expected that PSA would be lost through the kidney in nephrotic syndrome (and proteinlosing enteropathy) but no cases have been found in the literature.…”
Section: Psa In Non-prostatic Illnessmentioning
confidence: 99%